Variabel determinan pendapatan asli daerah di kota samarinda - Ardianta, Edu; Utary, Anis Rachma; Effendy, Aji Sofyan (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
This research aims to determine the effect of Capital Expenditures, Amount Companies, Economic Growth and Accountability to improve Local Own Revenue. The analytical model used in this research is using Multiple regressions Analysis. The data used are secondary data for the fiscal year 2005 to 2017.  The results of the analysis show that Capital Expenditures and Accountability have a positive not significant effect on Local Own Revenue. Amount Companies has a positive significant effect on Local Own Revenue. economic growth has negative significant effect on Local Own Revenue.